Study of Effect of Lactobacillus gasseri Filtrate on Growth of Some Pathogenic Fungi - AI-Marjani, l. F.; Abbod, z. H.; Abdalkarim, M.K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The inhibitory effect concentrated filtrate of local Lactobaciilus gasseri against Candida albicans and Trichophyton mentagrophytes, T ruhrum and Aspergillus flavus which were isolated from infected cases in human beings, tested using two methods :well diffu ion and Mixed with the mold medium (Sabouraud agar). The results showed that the concentrated filtrate of L. gasseri have inhibitory effect against Cundida ulbicans, the inhibition zone was 13 mm. As well as, the concentrated tiltrate inhibited, considerably Trichophyton mentagrophytes, T. rubrum and Aspergillus jlavus growth when the filtrate was mixed with Sabouraud agar, the inhibition activity was (57.6 , 41.2 , 66.6 )% against Trichophyton mentagrophytes, T.rubrum andAspergillusflavu.’i respectively. Results showed that concentrated filtrate of L.gasseri showed strong activity against T. mentagrophytest spores gcrminatio!l (the inhibition was 79.45%) by Mixing Lhfiltrate with the mold medium (Sabouraud agar).